Representation of National Identity Through Nusantara Cultural Symbols in Tifo La Grande Indonesia: A Cultural Communication Perspective - Setiadi, Christopher (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
In fostering unity within a nation, national identity is one of the important aspects to maintain the sustainability of unity and oneness. Furthermore, football as the most popular sport in the world also plays its role as a sport that can unite the existing diversity. This can be seen in the La Grande Indonesia tifo in the Indonesia vs China match in the 2026 World Cup Qualifiers group C. This tifo is present as a way of cultural communication as a means of conveying messages to the general public. In this study, the researcher applied a qualitative approach and phenomenological methods that exist in society related to the match. With the tifo image document study technique as a form of data collection technique, the study found that the La Grande Indonesia tifo displays a representation of national identity through cultural communication by displaying the figure of a warrior along with attributes from various tribes that are able to foster a sense of togetherness among people among the different tribes in Indonesia.